The Application of PjBL with STEM Integration: Its Effect on Science Problem-Solving Abilities - Subekti, Ananda Oktaviani; Rahayu, Rina; Trisnowati, Eli (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2025)
This study aims to investigate the effectiveness of the PjBL Model with the STEM Approach in improving junior high school students' science problem-solving abilities. It is a quasi-experiment with a nonequivalent control group design. The population is grade VIII students of State Junior High School 3 Magelang, and the sample is grade VIIIB and VIIIF students, established by using the purposive sampling technique, with VIII B students as the experimental class and VIIIF students as the control class. The data were collected using a test. The results showed the post-test scores of the experimental class were higher than those of the control class with the sig. (2-tailed) < 0.05, namely 0.000 from the independent sample t-test. The N-gain test shows that the N-gain of the experimental class is higher than that of the control class (0.678> 0.412), both in moderate criteria, so it can be concluded that the PjBL Model with the STEM Approach can improve the science problem-solving abilities of junior high school students.